Blockchain and IoT Integration for Secure Healthcare Data Management: A Narrative Review - Setiawan, Adi Wahyu (Indonesian Scientific Publication, 2025)
The convergence of blockchain and Internet of Things (IoT) technologies has the potential to revolutionize secure data management in healthcare systems. This narrative review investigates how this integration addresses critical issues such as data privacy, interoperability, energy efficiency, and systemic barriers in healthcare. Literature was gathered from databases including Scopus, Web of Science, and Google Scholar, using keyword combinations such as